ANALYSIS OF SOCIAL MEDIA UTILIZATION IN THE DIGITAL MARKETING OF UMRAH PRODUCTS AT PT ATHALAH SAFAR INTERNASIONAL METRO CITY - Nurni Fitriyana; Primadatu Deswara (Institut Agama Islam Negeri Metro, 2026)
The influence of social media on economic activities has grown significantly, making it an essential marketing tool for modern businesses. PT Athalah Safar Internasional is a travel agency that actively promotes its Umrah products through social media platforms, including Instagram, Facebook, TikTok, and WhatsApp. Considering the importance of digital marketing and increasing competition, the company needs effective strategies to attract prospective pilgrims. This study aims to analyze the use of social media in promoting Umrah products at PT Athalah Safar Internasional Metro City using SWOT analysis. The research employed a descriptive qualitative approach, with data collected through interviews and documentation. The findings show that the company’s strengths include effective social media management, collaboration with influencers and strategic partners, and a strategic location. However, limited human resources and inadequate infrastructure remain weaknesses. Opportunities arise from growing public interest in Umrah and the development of digital technology for marketing activities. In addition, intense competition, fake social media accounts and data security issues pose potential threats. As a result, the company should improve employee training, strengthen supporting infrastructure and expand its social media reach to enhance service quality and competitiveness.